Developing an activated biochar-mineral supplement for reducing methane formation in anaerobic fermentation - Sara Tahery; Mariano C. Parra; Paul Munroe; David R. G. Mitchell; Sarah J. Meale; Stephen Joseph (Biochar)
Abstract The effects of biochar on methane emissions from soils are well understood. However, biochar effects on methane production from livestock have received less attention. In this study, a biochar-mineral supplement for livestock was developed by pyrolyzing a mixture of wheat straw, aluminosilicates, iron sulfate, and zinc oxide at 600 ℃. The supplement was then activated using peracetic and propionic acids, and potassium nitrate. The activated biochar-mineral supplement was characterized using analytical techniques. A high surface area, a high concentration of oxygen-containing functional groups, and a high concentration of free radicals, associated with O and Fe unpaired electrons, assisted the supplement with catalysing the oxidation of methane. Microstructural analysis of the supplement suggested the formation of organo-mineral phases, rich in C, O, Fe, Si, Al, K and Ca, indicating that the biochar reacted with mineral additives to preserve them. To assess the potential of the supplement to reduce methane produced form livestock, an in vitro batch culture incubation was conducted (n = 3) with rumen fluid sourced from Holstein–Friesian steers. The supplement was incubated at inclusion rates of 0% (control), 1.5%, 4.0% and 6.0% of dry matter (DM), with a Rhodes grass hay substrate. Compared to the control, the supplement reduced cumulative gas production by 10.1% and 12.7% and methane production by 19.03% and 29.32% after 48 h when included at 4.0% and 6.0% DM (P < 0.05), respectively, without causing any detrimental impacts on fermentation parameters. The supplement assisted with reducing the concentration of dissolved mineral nutrients, such as P and Mg, when included at 4.0% and 6.0% DM (P < 0.05). Graphical abstract